Natural Pozzolans a Comparative Study: A Review. Issue 1 (April 2020) - Shukla, Ashish; Gupta, Nakul; Gupta, Ankur; Goel, Rajesh; Kumar, Sanjeev
Abstract: Exploitation of Natural Pozzolans (Calcined Clay, Calcined Shale & Metakaolin) as Supplementary Cementitious materials (SCMs) for mortar and concrete has attended goodish observance in last decades. In this content the NP used in vast range in partial substitution of cement in concrete and mortar, and due to its pozzolanic behavior, it improves the performance of concrete and mortar strength and durability. The minimization of carbon-dioxide emissions in the cement industry due to the increasing involvement of NP(Natural Pozzolans). The different proportions of NP as partial substitute results in enhancing the comp. strength, water absorption, sorptivity etcetera and it gives the resistance to the structure of mortar and concrete to action of harmful solution.